Innovations in chronic pain treatment (Research, Society and Development, 2022)
Objective: Chronic pain occurs when the painful sensation persists for more than three months. It affects about 30% of patients and is the main reason for seeking medical attention and using drugs. Drug therapy is an important tool that aims to increase the individual's quality of life, as well as non-drug therapy in a multidisciplinary approach. Thus, this study aimed to evaluate new treatment options to address chronic pain. Methodology: A literature review was carried out using the descriptors “updates”, “management”, “chronic pain” in the following databases: PubMed; Scientific Electronic Library Online (SCIELO); Latin American and Caribbean Literature in Health Sciences (LILACS), in addition to the books “Miller Anestesia” 9th ed and Treaty of Musculoskeletal Pain, from the Brazilian Society of Orthopedics and Traumatology. Results and Discussion: Currently, there are several drugs available, the main ones being: opioids, nonsteroidal anti-inflammatory drugs, antidepressants, antiepileptics and serotonergic compounds. Studies on the use of cannabinoids have grown in recent years, but there is still no evidence for its use as a first-line treatment in this pathology. Opioids are effective for pain of oncological origin, while those derived from other pathophysiological processes respond better to other available options, such as dual antidepressants or antiepileptics. It is important to include physical activity, psychotherapy and physiotherapy when necessary. In addition, botulinum toxin has gained prominence for its effectiveness in the intervention. Conclusion: Chronic pain is a complex disease that involves organic and emotional processes and requires pharmacological and non-pharmacological management.